ANALISIS JUMLAH KREDIT TERSALURKAN PADA BANK UMUM DI INDONESIA (PARTIAL ADJUSTMENT MODEL) - B01108003, Mirsa Maulida (Jurnal Pembangunan dan Pemerataan, 2012)
The title of this research is Analisis Jumlah Kredit Tersalurkan pada Bank Umum di Indonesia (Partial Adjustment Model). The objective of this research is to analyze the influence of Third Party Funds (TPF), Non-Performing Loans (NPL), Capital Adequacy Ratio (CAR), Return on Assets (ROA) and the amount of credit that channeled in the previous quarter (JKT-1) to the amount of credit that channeled to the banks in Indonesia. This research used time series data in the period of 2001 first quarter 2011 fifth quarter, which is a secondary data from Banking Statistics of Indonesia. The method of this research is multiple linear regression (Partial Adjustment Model). According to the result of estimation, this research find that factors affect significantly to the amount of credit that channeled to the banks in Indonesia is TPF, NPL, CAR and JKT-1. And the variable that affect not significantly is ROA. And then, variable that affect positively is TPF and JKT-1. And variables that affect negatively is NPL, CAR and ROA. Keywords: The amount of credit that channeled to the banks in Indonesia, TPF, NPL, CAR, ROA and the amount of credit that channeled in the previous quarter (JKT-1).